(E)-3-Propoxymethylidene-2,3-dihydro-1H-pyrrolo[2,1-b]quinazolin-9-one monohydrate - Elmuradov, Burkhon Zh (International Union of Crystallography, 2010)
The title compound, C(15)H(16)N(2)O(2)·H(2)O, was synthesized via the alkylation of 3-hydroxymethylidene-2,3-dihydro-1H-pyrrolo[2,1-b]quinazolin-9-one with n-propyl iodide in the presence of sodium hydroxide. The organic molecule and the water molecule both lie on a crystallographic mirror plane. In the crystal structure, intermolecular O—H⋯O and O—H⋯N hydrogen bonds link the components into extended chains along [100].